KAJIAN EKONOMI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) BENUIS - Normansyah Normansyah (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
energy as a source of electrical energy, both solar, wind, hydro and other renewable energy sources, a potential source of uranium in Indonesia.What needs attention is how to design energy policies to use each type of energy optimally, so as to avoid over-exploitation of fossil energy on the one hand, and on the other hand prevent neglect of renewable energy sources. In an effort to overcome this, the central and regional governments have made new policies that encourage the use of renewable energy sources as an alternative to supplying electricity to rural communities.The aims and objectives of the Feasibility Study Preparation Activity for the Benuis Micro-hydro Power Plant (PLTMH) Benuis Village, Selimbau District are; Availability of technical documents that describe the detailed design of the PLTMH and the Budget Plan (RAB) for the Benuis PLTMH Benuis Village. As a proposal for the construction of network facilities and infrastructure electricity..